This theorem allows us to convert a log of a product to a sum of the log of each operand.
For example:
log2(8 ⋅ 16) = (log28) + (log216)
log2(8 ⋅ 16) = 3 + 4
log2(8 ⋅ 16) = 7
Before calculators were invented, multiplying large numbers would take a long time. People used the Log Product Rule to convert multiplication problems to addition problems which are easier to solve.
Let's try multiplying two numbers using the following algorithm:
- Calculate log base 10 of both operands using a log table.
- Add the results.
- Calculate 10 to the power of the result from step 2 using an "anti-log" table.
For example, suppose we want to calculate 14⋅18.
First, we calculate:
log10(14 ⋅ 18)
This is equal to
(log1014) + (log1018)
Then, the log table tells us that:
log1014 = 1.146
log1018 = 1.255
Thus:
(log1014) + (log1018) = 2.401
Finally, the anti-log table tells us that:
102.401 = 251.77
14⋅18 = 252, so we came quite close to the answer.
The key to proving this theorem is the following exponentiation property:
xm ⋅ xn = x(m+n)
Quiz (1 point)
- (xm) ⋅ (xn) = x(m + n)
if logxz = p, then xp = z
if logxz = p, then xp = z
if logxz = p, then xp = z
if the following are true:
- a = x
- b = y
- c = x ⋅ y
then c = a ⋅ b
if the following are true:
- a = b
- b = c
then a = c
if bm = bn, then m = n
if the following are true:
- a = x
- b = y
- c = z
- z = x + y
then c = a + b
Please write your proof in the table below. Each row should contain one claim. The last claim is the statement that you are trying to prove.